Consecutive Alkynylation–Michael Addition–Cyclocondensation (AMAC) Multicomponent Syntheses of α-Pyrones and α-Pyridones - Breuer, Natascha; Müller, Thomas J. J. (Synthesis, 2018)
A novel consecutive three-component synthesis of α-pyrones is based upon an alkynylation–Michael addition–cyclocondensation (AMAC) sequence, starting from (hetero)aroyl chloride and terminal alkyne to furnish the alkynone which reacts with malonates to give the α-pyrones in moderate to very good yields. By concatenating ammonolysis of the α-pyrones, an alkynylation–Michael addition–cyclocondensation–ammonolysis (AMACA) synthesis of α-pyridones can be conceived. α-Pyridone products with and without ester functionality are obtained in moderate yields.
Keywords: multicomponent reactions; C–C coupling; cyclocondensation; alkynes; heterocycles; palladium